Fabrication of highly efficient and stable indirect Z-scheme assembly of AgBr/TiO 2 via graphene as a solid-state electron mediator for visible light induced enhanced photocatalytic H 2 production - Shehzad, N. (2019)
In this study, indirect Z-schematic assembly of AgBr and TiO 2 via graphene as a solid-state electron mediator was developed and investigated for photocatalytic H 2 production. The AgBr/rGO/TiO 2 was fabricated using facile two-step synthesis method which includes the growth of AgBr and deposition of TiO 2 on graphene oxide sheets followed by partial reduction through reflux method. The photocatalysts were characterized using TEM, XRD, XPS, FTIR, nitrogen (N 2 ) adsorption and desorption, Raman, PL and UVâVis spectroscopy to understand morphology, structure, chemical and optical properties. Alterations in band structures, elevation of conduction band positions and reduction in band gap energies of rGO-modified AgBr/TiO 2 photocatalysts were evaluated. The performance of AgBr/rGO/TiO 2 exhibited 2025 ppm of H 2 production, which was 7 fold higher than AgBr/TiO 2 (289 ppm), 2.3 fold higher than rGO/TiO 2 (885 ppm) and 13.4 fold higher than TiO 2 (151 ppm). Enhanced photocatalytic activity of Z-schematic composites can be attributed to strong interfacial bonding (AgBrârGOâTiO 2 ), efficient transfer of electrons due to synergistic effect of AgBr and rGO as well as extended light absorption due to highly light sensitive AgBr. In addition, yield of H 2 production was decreased above 5 AgBr loading and dosage of 0.10 g of photocatalyst due to incompatibility of ratio and shielding effect of particles. Moreover, with increase of temperature and concentration of hole scavenger, yield of H 2 production was gradually increased which demonstrated the contribution of H 2 from photoreforming of hole scavenger. Based on the experimental and characterizations results, a possible mechanism that highlighted the surface redox reactions and charge transfer pattern on AgBr/rGO/TiO 2 was developed. Thus, indirect Z-scheme assembly of AgBr/rGO/TiO 2 could be a promising photocatalyst for solar energy assisted H 2 production. Â© 2018 Elsevier B.V.